Changes in lung function and exercise capacity are strong predictors of mortality in patients with IPF receiving antifibrotic therapy - Oh, Ju Hyun; Park, Moo Suk; Chung, Man Pyo; Jeong, Sung Hwan; Song, Jin Woo; Choi, Sun Mi; Kim, Yong Hyun; Park, Sung Woo; Jegal, Yangin; Yoon, Hee-Young; Choi, Won-Il; Yoo, Jung-Wan; et al. (Frontiers in Medicine, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic fibrosing interstitial pneumonia with poor prognosis. This study evaluated whether monitoring changes in lung function and exercise capacity during antifibrotic therapy offers superior prognostic value compared with baseline clinical parameters in IPF.MethodsWe retrospectively analyzed patients with IPF enrolled with the Korean IPF cohort registry between June 2016 and August 2021. Prognostic factors for mortality were assessed using Cox proportional hazards models and receiver operating characteristic (ROC) curve analysis.ResultsAmong 1,229 patients (mean age 68.3 years; 82.8% male), 88.0% received antifibrotic therapy. During a median follow-up of 41.0 months, 37.9% of the treated patients died. Multivariable Cox analysis revealed that a decline in forced vital capacity (FVC) at 12 months, lower baseline diffusing capacity of the lungs for carbon monoxide (DLco), a decline in DLco at 12 months, and a reduction in the 6-min walk distance at 6 months, were independent risk factors for mortality in IPF patients receiving antifibrotic therapy. In the ROC curve analysis, the change in FVC at 12 months showed the highest predictive accuracy for mortality (area under the curve = 0.676; p < 0.001). Kaplan–Meier analysis demonstrated significantly poorer survival in patients with ≥5.8% decline in FVC and ≥11.5% decline in DLco over 12 months (p < 0.001 and p = 0.001, respectively).ConclusionLongitudinal changes in lung function and exercise capacity as indicators of response to antifibrotic therapy may serve as potential surrogate markers of mortality in patients with IPF.